Two new species of the water mite family Pontarachnidae (Acari: Hydrachnidia), with a discussion of the taxonomic status of Pontarachna hinumaensis Imamura - Smit, Harry (Zootaxa, 2002)
Two new species are described of the predominantly marine water mite family Pontarachnidae, i.e. Pontarachna africana n. sp. from South Africa and Litarachna hongkongensis n. sp. from Hong Kong, China. Pontarachna hinumaensis Imamura, 1958 is synonymized with P. anellata Sokolov, 1936. A checklist is provided of all known species of Pontarachnidae, including their geographical distribution.